The Johor Government's Interaction with Europe: An Analysis of Hikayat Johor dan Tawarikh Almarhum Sultan Abu Bakar (Malay Literature, 2023)
The Johor government is a Malay government that has a long history. Since its establishment in 1528, the Johor government has been recorded to be ruled by three different nobilities, namely the Sultan, the Bendahara and the Temenggung, all of whom have witnessed every transition of power, alongside its complex historical event. Although the Johor Sultanate is the descendant of the Malaccan Sultanate, the Johor government is not an exception to political turmoil and shifts. The Johor government was able to endure for a long period in bucking the tide of time until it finally succeeded in establishing itself in the era of modernization under the reign of Sultan Abu Bakar. In this regard, this paper aims to identify the interaction between the Johor government under the reign of Sultan Abu Bakar with Europe until the Johor government was nicknamed the modern government. This qualitative study uses the Malay historiography manuscript entitled Hikayat Johor dan Tawarikh Almarhum Sultan Abu Bakar as its data. The analysis using the Theory of Forms of Interaction and Social Environment between Civilizations found that the interactions between the Johor government occured in the context of a partnership involving sociocultural and technological as well as political cooperation. Based on the results of the study, it can be concluded that Sultan Abu Bakar was a wise ruling figure in establishing interactions with Europe, thus earning the title as the Father of Johor Modernization.Full text: PDF